Addendum: a second Poem by Eduard Dorsch on the occasion of Humboldt’s 100th birthday - Andress, Reinhard (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2019)
AbstractIn a previously published article in HIN under the title of “Eduard Dorsch and his unpublished poem on the occasion of Humboldt’s 100th birthday,” I elaborated on Dorsch’s poem that was read in Detroit in front of a German-American audience on Sept. 14, 1869, a day widely celebrated in the US in honor of Humboldt. Although it was not surprising that Dorsch wrote the occasional poem in the first place given his affinities with Humboldt’s world of thought, a discovery of a second occasional poem upon further research in Dorsch’s voluminous papers was indeed unexpected, in this case read on the same date in Monroe, Michigan. Although there are a number of similarities between the Detroit and Monroe versions, there are enough differences that warrant this addendum to my original article.ZusammenfassungIn einem bereits in HIN veröffentlichten Artikel mit dem Titel Eduard Dorsch und sein unveröffentlichtes Gelegenheitsgedicht zu Humboldts 100. Geburtstag ging ich auf Dorschs Gedicht ein, das am 14. September 1869 vor einem deutsch-amerikanischen Publikum in Detroit verlesen wurde, an einem Tag, der überall zu Ehren Humboldts in den USA gefeiert wurde. Obwohl es nicht überraschend ist, dass Dorsch angesichts seiner Affinität zu Humboldts Gedankenwelt das Gedicht überhaupt schrieb, war der Fund eines zweiten Gelegenheitsgedichts in Dorschs umfangreichem Nachlass dennoch unerwartet, in diesem Falle am selben Tag in Monroe, Michigan verlesen. Obwohl es eine Reihe von Ähnlichkeiten zwischen den Detroit- und Monroe-Versionen gibt, tauchen auch genug Unterschiede auf, um diesen Nachtrag zu meinem ursprünglichen Artikel zu rechtfertigen.ResumenEn un artículo ya publicado en HIN bajo el título de "Eduard Dorsch y su poema inédito con motivo del centenario de Humboldt", abordé el poema de Dorsch leído en Detroit frente a una audiencia germano-estadounidense el 14 de septiembre de 1869, un día ampliamente celebrado en los Estados Unidos en honor a Humboldt. Aunque no sorprende que Dorsch escribiera el poema de ocasión debido a sus afinidades con la cosmovisión de Humboldt, lo inesperado fue el hallazgo de un segundo poema para la misma ocasión durante un estudio adicional de los voluminosos papeles de Dorsch. Este segundo poema fue leído en la misma fecha en Monroe, Michigan. Si bien existe una serie de similitudes entre las versiones creadas para Detroit y Monroe, también hay suficientes diferencias que justifican este apéndice a mi artículo original.
Keywords: Eduard Dorsch; occasional poem; Humboldt's 100th birthday